Effect of a solar lighting intervention on fuel-based lighting use and exposure to household air pollution in rural Uganda: A randomized controlled trial - Wallach, Eli S.; Lam, Nicholas L.; Nuwagira, Edwin; Muyanja, Daniel; Tayebwa, Mellon; Valeri, Linda; Tsai, Alexander C.; Vallarino, Jose; Allen, Joseph G.; Lai, Peggy S. (Indoor Air, 2022)
Solar lighting is an alternative to polluting kerosene and other fuel-based lighting devices relied upon by millions of families in resource-limited settings. Whether solar lighting provides sustained displacement of fuel-based lighting sources and reductions in personal exposure to fine particulate matter (PM2.5) and black carbon (BC) has not been examined in randomized controlled trials. Eighty adult women living in rural Uganda who utilized fuel-based (candles and kerosene lamps) and/or clean (solar, grid, and battery-powered devices) lighting were randomized in a 1:1 ratio to receive a home solar lighting system at no cost to study participants (ClinicalTrials. gov NCT03351504). Among intervention group participants, kerosene lamps were completely displaced in 92% of households using them. The intervention led to an average exposure reduction of 36.1 μg/m3 (95% CI −70.3 to −2.0) in PM2.5 and 10.8 μg/ m3 (95% CI −17.6 to −4.1) in BC, corresponding to a reduction from baseline of 37% and 91%, respectively. Reductions were greatest among participants using kerosene lamps. Displacement of kerosene lamps and personal exposure reductions were sustained over 12 months of follow-up. Solar lighting presents an immediate opportunity for achieving sustained reductions in personal exposure to PM2.5 and BC and should be considered in household air pollution intervention packages.
Keywords: Back carbon; Energy access; Household air pollution; Kerosene; Lighting; Solar home system; Fine particulate matter (PM2.5)